Adverse childhood experiences (ACEs), peer victimization, and substance use among adolescents. (August 2020) - Afifi, Tracie O.; Taillieu, Tamara; Salmon, Samantha; Davila, Isabel Garcés; Stewart-Tufescu, Ashley; Fortier, Janique; Struck, Shannon; Asmundson, Gordon J.G.; Sareen, Jitender; MacMillan, Harriet L.
Abstract: Background: Adverse childhood experiences (ACEs) are common and related to substance use problems in adulthood. Less is known about these relationships in adolescence and if experiencing ACEs in addition to peer victimization (or bullying) would have an interaction or cumulative effect on the odds of adolescent substance use. Method: Data were used from the Well-Being and Experiences Study (The WE Study), a cross-sectional survey of adolescents aged 14–17 years (n = 1002) in Manitoba, Canada collected between July 2017 and October 2018. Statistical methods included descriptive statistics and logistic regression models. Results: The prevalence of experiencing any of the 12 ACEs was 75.1 %. The prevalence of any peer victimization (monthly or more often) was 24.1 %. All individual ACEs were associated with increased odds of substance use. No significant interaction effects between ACEs and peer victimization on substance use were found. Significant cumulative effects were found, indicating that experiencing both ACEs and peer victimization, compared with experiencing ACEs only, significantly increased the odds of substance use among adolescents. Conclusion: The odds of substance use becomes significantly greater if the adolescent with a history of ACEs also experiences peer victimization. Further research aimed at effective prevention of ACEs, peer victimization, and substance use is needed.